A comparison of patient-centered economic and clinical outcomes of post-mastectomy breast reconstruction between obese and non-obese patients. (December 2016) - Huo, Jinhai; Smith, Benjamin D.; Giordano, Sharon H.; Reece, Gregory P.; Tina Shih, Ya-Chen
Abstract: Background: The objectives of this study were to compare, by patient obesity status, the contemporary utilization patterns of different reconstruction surgery types, understand postoperative complication profiles in the community setting, and analyze the financial impact on health care payers and patients. Methods: Using data from the MarketScan Health Risk Assessment Database and Commercial Claims and Encounters Database, we identified breast cancer patients who received breast reconstruction surgery following mastectomy between 2009 and 2012. The Cochran-Armitage test was used to evaluate the utilization pattern of breast reconstruction surgery. Multivariable logistic regressions were used to estimate the association between obesity status and infectious, wound, and perfusion complications within one year of surgery. A generalized linear model was used to compare total, complication-related, and out-of-pocket costs. Results: The rate of TE/implant-based reconstruction increased significantly for non-obese patients but not for obese patients during the years analyzed, whereas autologous reconstruction decreased for both patient groups. Obesity was associated with higher odds of infectious, wound, and perfusion complications after TE/implant-based reconstruction, and higher odds of perfusion complications after autologous reconstruction. The adjusted total healthcare costs and out-of-pocket costs were similar for obese and non-obese patients for either type of breast reconstruction surgery. Conclusions: A greater likelihood of one-year complications arose from TE/implant-based vs autologous reconstruction surgery in obese patients. Given that out-of-pocket costs were independent of the type of reconstruction, greater emphasis should be placed on conveying the surgery-related complications to obese patients to aid in patient-based decision making with their plastic surgeons and oncologists. Highlights: A decreasing trend in autologous reconstruction, with the trend most pronounced among non-obese patients. High rates of infectious and wound complications for obese patients with TE/implant-based reconstruction. Total health care and out-of-pocket costs were comparable based on obesity status with either type of reconstruction surgery.